2007
DOI: 10.1002/cne.21400
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 26RFa binding sites and GPR103 mRNA in the central nervous system of the rat

Abstract: The novel RFamide peptide 26RFa, the endogenous ligand of the orphan receptor GPR103, affects food intake, locomotion, and activity of the gonadotropic axis. However, little is known regarding the localization of 26RFa receptors. The present report provides the first detailed mapping of 26RFa binding sites and GPR103 mRNA in the rat central nervous system (CNS). 26RFa binding sites were widely distributed in the brain and spinal cord, whereas the expression of GPR103 mRNA was more discrete, notably in the midb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 90 publications
5
76
1
3
Order By: Relevance
“…Accordingly, 26RFa was found to display moderate affinity and selectivity for NPFF2, the receptor of neuropeptide FF, another member of the RFamide family (47). Moreover, NPFF and prolactin-releasing peptide (PrRP), both with high affinity for NPFF2 receptor (9), displaced [ 125 I]-26RFa binding in brain regions enriched with NPFF2 receptor (48). Interestingly, NPFF2 receptor is coupled to G i/o protein, in agreement with our finding showing loss of 26RFa insulinostatic effect in b-cells and human islets treated with PTX.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, 26RFa was found to display moderate affinity and selectivity for NPFF2, the receptor of neuropeptide FF, another member of the RFamide family (47). Moreover, NPFF and prolactin-releasing peptide (PrRP), both with high affinity for NPFF2 receptor (9), displaced [ 125 I]-26RFa binding in brain regions enriched with NPFF2 receptor (48). Interestingly, NPFF2 receptor is coupled to G i/o protein, in agreement with our finding showing loss of 26RFa insulinostatic effect in b-cells and human islets treated with PTX.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNAs encoding 26RFa/QRFP and its cognate receptor QRFPR are highly expressed in the dorsolateral and mediobasal hypothalamic areas of rodents (Chartrel et al 2003, Takayasu et al 2006, Bruzzone et al 2007). …”
Section: Comparative Aspects Of Biological Actions Of 26rfa/qrfp In Vmentioning
confidence: 99%
“…Neuroanatomical observations revealed that 26RFa-and GPR103-expressing neurons are primarily localized in hypothalamic nuclei involved in the control of feeding behavior (1,2,5,7). Indeed, intracerebroventricular administration of 26RFa or 43RFa stimulates food intake (1,5,8,9), and the neuropeptide exerts its orexigenic activity by modulating the neuropeptide Y/proopiomelanocortin system in the arcuate nucleus (9).…”
mentioning
confidence: 99%